ANOMALI GAYA BERAT, KEGEMPAAN SERTA KELURUSAN STRUKTUR GEOLOGI DAERAH JOGJAKARTA DAN SEKITARNYA - S.Widijono, Bambang; Setyanta, Budi (Jurnal Geologi dan Sumberdaya Mineral, 2007)
The region of Jogjakarta and the surrounding area which are generaly covered by young sediment, consist of aluvium and volcanic deposits. Because of this phenomenon, lateral and vertical distribution of geological structural element are still unknown. Therefore, gravity data analysis is a good tool to delineate geological structural element burried by young sedimentdeposits. Regional and local geological structural lineaments which are detected by Bouguer and residual gravity anomaly analyses, inform that deformation processes have occurred intensively in this area. The occurrences of east-west trending fold and northeast-southwest trending thrust fault, northwest-southeast trending strikeslip fault, and north-south trending normal fault indicate that deformation process was caused by north-south compressional principal stress generated by subduction Eurasian plate and Indo-Australian plate. Gravity modelling analysis of AB and CD sections indicate the presence of strike slip fault, thrust fault and normal fault within the basement and Tertiary rocks. Several faults, such as Bogowonto, Nanggulan, Sentolo, Imogiri and Opak Faults, are interpreted to be reactivated and faulted the Quarternary deposits. Earthquake hazard that took place in Jogjakarta and th surrounding area on May 27 , 2006 by the reactivation of Opak Fault. Referring to this experience, the study of active faults in this area is necessary. Keywords : anomaly, gravity, geological structure, earthquake